Is It Possible to Apply Inquiry in the First Level of Primary School without Hindering the Acquisition of Scientific Competencies? Perspectives of Pupils and Their Pre-Service Teacher - Jaime Delgado-Iglesias; Javier Bobo-Pinilla; Roberto Reinoso-Tapia; María Victoria Vega-Agapito (MDPI AG, 2024)
The aim of this study is to assess the application of inquiry as a teaching strategy during the practicum of a pre-service teacher and to verify the acquisition of scientific skills by her students. The importance of this study is the application of inquiry as a teaching strategy at lower levels of basic education to contribute to scientific skills and scientific literacy. The sample consisted of 27 pupils in the first level of primary education and one pre-service teacher in a Spanish school. The methodology used was a case study with a participatory experimental design, incorporating guided discovery and teacher questioning focused on plant growth. The results indicate that the pupils improved their understanding and assimilation of content related to plant functions, scientific procedures, and critical thinking. The pre-service teacher demonstrated mastery of the inquiry-based methodology, confirming an adequate level of both pedagogical and scientific competence. Some suggestions are provided to enhance her training. The study concludes by demonstrating that it is possible to implement inquiry at any educational level, despite the potential limitations of the students. It is recommended that pre-service teachers receive comprehensive training to enable them to facilitate the acquisition of scientific competence among their students.